Self-employment and business cycles: searching for asymmetries in a panel of 23 OECD countries - Carmona, Mónica; Congregado, Emilio; Golpe, Antonio A.; Iglesias, Jesus (Journal of Business Economics and Management, 2016)
The aim of this work is to identify whether the bidirectional relationship between entrepreneurship cycles and output gaps is asymmetric depending on the phase of the business cycle. To this end, we employ a panel threshold regression model in which different relations can prevail in each regime, defined by the values of the threshold variable. The findings of this article qualify previous empirical results. In particular, our estimates provide support for the existence of different responses – both in terms of sign and magnitude – of cyclical self-employment to output growth and of output growth to cyclical self-employment, depending on the value of the threshold variable. The result is highly important for policy makers and practitioners given that whether they ignore the asymmetric impact that an entrepreneurship promotion policy action might have on the real economy, the action might lead to unexpected effects.